The correlation between embryo rescue and hormonal changes in seedless grapes - Li, Guirong; Li, Kaiwei; Lu, Yihai; Fan, Xiucai; Wang, Ling (Frontiers in Plant Science, 2024)
After normal pollination and fertilization of pseudoparthenocarpic seedless grapes, their embryos often stop developing due to certain developmental factors, resulting in embryo abortion. Hybrid breeding using seedless grapes as the maternal parent requires embryo rescue breeding technology. This technology plays a crucial role in seedless grape breeding. Although previous studies have extensively explored this technology, knowledge regarding its impact on embryo abortion and the effectiveness of rescue techniques remains limited. This study aimed to investigate the correlation between embryo rescue and hormonal changes in seedless grapes. Four Eurasian seedless grape cultivars, such as "Thompson Seedless," "Flame Seedless," "Heshi Seedless," and "Ruby Seedless," were selected for examination. We investigated endogenous hormone levels, including indole-3acetic acid (IAA), gibberellic acid (GA 3 ), and abscisic acid (ABA), in both berries and in vitro ovules during the most suitable embryo rescue time for these cultivars. Based on the observed fluctuations in endogenous hormone levels and previous research findings, appropriate doses of exogenous hormones, such as IAA, GA 3 , and ABA, were applied during seedless grape embryo rescue. The results indicated significant differences in endogenous hormone levels between berries with varying ovule counts of the same cultivar and ovules cultured in vitro, suggesting hormonal influence on ovule abortion and embryo development in seedless grapes. Further research has identified effective ratios of exogenous hormones: 30 mg•L -1 IAA + 30 mg•L -1 ABA for berry ovule development, 1.0 mg•L -1 IAA + 2.0 mg•L -1 6-benzylaminopurine (6-BA) + 1.0 mg•L -1 GA 3 + 1.0 mg•L -1 ABA for in vitro ovule development, and 1.0 mg•L -1 IAA + 2.0 mg•L -1 6-BA + 1.0 mg•L -1 GA 3 for embryo germination and seedling formation. In summary, hormonal changes significantly influence ovule and embryo development and are closely related to seedless grape embryo rescue breeding. This study deepened our understanding of the correlation between seedless grape embryo rescue and hormonal changes. It also resulted in successfully producing a batch of embryo rescue seedlings, further enhancing embryo rescue breeding technology and providing new germplasm materials for developing new seedless grape cultivars.